EXPERIMENTAL STUDY ON RHEOLOGICAL BEHAVIOR OF022Cr18Ni14Mo2 STAINLESS STEEL AT HIGH TEMPERATURE AND HIGH STRAIN RATE - JIA HaiShen; ZHANG JiLin; YI XiangBin; LUO WenCui (Jixie qiangdu)
To explore the influence of external temperature and loading rate on itsrheological behavior and mechanism, the dynamic impact compression test was conducted on 022 Cr18 Ni14 Mo2 stainless steel by using the split Hopkinson compression bar test platformat at 2 000 s-1～5 000 s-1 and 25℃～400℃.The results show that the flow stress, strain rate sensitivity, strain hardening and temperature sensitivity of the sample are closely related to strain, temperature and strain rate. At a constant temperature, the flow stress, strain hardening effect, and strain rate sensitivity increase with the increase of strain rate.At a constant strain rate, the temperature sensitivity increases with the increase of temperature, and the sample exhibits a significant thermal softening effect. The strain rate sensitivity and strain hardening effect appear to weaken with increasing temperature. In addition, the microstructure observation by scanning electron microscope（SEM） shows that deformation twins are mainly present in the grains, and a deformation zone with positioning or stacking faults is present in the grains. Under high strain rate or low temperature conditions, the number of deformation zone in the grain is more. The deformation twins within the grains help to adjust the degree of deformation between the grains and improve the uniformity of sample deformation at high strain rate.